Efficiency of four secondary enrichment protocols in differentiation and isolation of Listeria spp. and Listeria monocytogenes from smoked fish processing chains - Duarte, Gabriela (2011)
Four secondary enrichment protocols (conventional methods: UVM II, Fraser 24 h and Fraser 48 h: Impedimetric method: Listeria electrical detection medium) were studied for their ability to isolate Listeria spp. and Listeria monocytogenes from fish and environmental samples collected along the processing chain of cold-smoked fish. From all methods, Listeria spp. and L. monocytogenes were respectively present in 56 and 34 of 315 samples analysed. Fraser broth incubated for 48 h gave the fewest false negative Listeria spp. results [4/56; (7.1%)], but concurrently only 15/34 (44.1%) samples were correctly identified as containing L. monocytogenes. Listeria electrical detection (LED) medium detected only 36/56 (64.3%) Listeria spp. positive samples. Despite this lower isolation rate, LED identified 20/34 (58.8%) L. monocytogenes positive samples correctly and gave fewer false positive results. The overall conclusion was that more than one isolation method is needed to accurately estimate L. monocytogenes contamination rates.